2016
DOI: 10.2144/000114432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluorescent Intercalating Dyes for Quantitative Loop-Mediated Isothermal Amplification (qLAMP)

Abstract: Real-time or quantitative loop-mediated isothermal amplification (qLAMP) is a promising technique for the accurate detection of pathogens in organisms and the environment. Here we present a comparative study of the performance of six fluorescent intercalating dyes-SYTO-9, SYTO-13, SYTO-82, SYBR Green I, SYBR Gold, EvaGreen-in three different qLAMP model systems. SYTO-9 and SYTO-82, which had the best results, were used for additional enzyme and template titration studies. SYTO-82 demonstrated the best combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 25 publications
(17 reference statements)
1
70
0
3
Order By: Relevance
“…More recently, several research groups have reported the use of other dyes for end-point reads of LAMP assays, with potential applications for ZIKV. These include malachite green dye [72,73], hydroxynaphthol blue dye [74,75], evagreen dye [76,77], Goldview II dye [78], Gelred dye [79,80], SYTO fluorescent dye [81,82], and berberine dye [83].…”
Section: Step 3: Lamp Modes Of Outputmentioning
confidence: 99%
“…More recently, several research groups have reported the use of other dyes for end-point reads of LAMP assays, with potential applications for ZIKV. These include malachite green dye [72,73], hydroxynaphthol blue dye [74,75], evagreen dye [76,77], Goldview II dye [78], Gelred dye [79,80], SYTO fluorescent dye [81,82], and berberine dye [83].…”
Section: Step 3: Lamp Modes Of Outputmentioning
confidence: 99%
“…Because SYBR Green I dye has several limitations, including inhibition of PCR, preferential binding to CG-rich sequences and effects on MCA, two intercalating dyes SYTO-13 and SYTO-82 were tried and did not show these negative effects, and SYTO-82 demonstrated a 50-fold lower detection limit (64), as well as best combinations of time-to threshold (Tt) and signal-to-noise ratio (SNR) (65). To optimize performance of the buffer, a PCR mix supplemented with two additives, 1M 1,2-propanediol and 0.2 M trehalose, were shown to decrease T m , efficiently neutralize PCR inhibitors, and increase the robustness and performance of qPCR with short amplicons (66).…”
Section: Melting Curve Analysis (Mca)mentioning
confidence: 99%
“…Well optimized LAMP assay shows sensitivity comparable to that of PCR, less than 10 copies per reaction [12]. Intercalating fluorescent dyes are compatible with LAMP reaction so that we can observe amplification in real-time [13]. Because amplification efficiency of LAMP reaction is very high, changes in reaction mixture components made it possible to detect the result with colorimetric detection methods [14][15][16].…”
Section: Introductionmentioning
confidence: 99%